1965
DOI: 10.1139/p65-192
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the Raman Spectrum of Solid Hydrogen With Ortho–para Ratio

Abstract: The frequencies and shapes of the vibrational Raman lines, Ql(0) and Q l ( l ) , of solid hydrogen a t 2.1 'I< have been studied for a series of ortho-para rat~os, c,/c,. In the concentration range 0.75 > c, > 0.20 and 1.0 > c, > 0.25, each Q line has a single maximum, and can be interpreted in terms of traveling vibrational excitations. For c0 < 0.20 the Q l ( l ) line splits into a band of closely spaced lines; a t these low concentrations traveling ortho excitat~ons apparently cannot be sustained, and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1967
1967
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…9,5,37 The Q 1 (J) energy dependence on c(1) reveals the coupling of the molecular vibrational states. The frequency shift for both density and c(J) from the respective gas phase line is 8,36,38,39 …”
Section: B Review Of Vibrational Raman Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…9,5,37 The Q 1 (J) energy dependence on c(1) reveals the coupling of the molecular vibrational states. The frequency shift for both density and c(J) from the respective gas phase line is 8,36,38,39 …”
Section: B Review Of Vibrational Raman Spectramentioning
confidence: 99%
“…The intensity of the Q 1 (J) lines are strongly dependent on c(1) in pure H 2 and D 2 . 3,8,38,39 There is an enhanced intensity of the lower energy Q 1 (1) line because, classically, the vibrating J ϭ 1 molecule drives neighboring J ϭ 0 molecules below their vibrational resonant frequency. 2 Thus, the Q 1 (1)/Q 1 (0) intensity ratio is described by…”
Section: B Review Of Vibrational Raman Spectramentioning
confidence: 99%
“…This conclusion is reinforced by the consideration that the present model, with its regular arrangement of imBy the principle of spectroscopic stability, any increase in the total intensity of the impurity line is matched by a decrease in the total intensity of the matrix line. Thus the ratio of the intensity of the matrix line per matrix molecule to that due to an isolated molecule is We now consider the lowest paradeuterium concentration, 6=3.7%, at which measurements have been made, 11 corresponding to one impurity molecule in 27. One can arrange such a concentration of impurities in a fee matrix in a very symmetric way in which every third molecule on any given line is an impurity.…”
Section: E K =-2e'[cos(k X A) Cos(k Y A)+co$(k Y A) Cos(k Z A) + Cos(mentioning
confidence: 99%
“…This work has grown out of study of the observed 11 unexpectedly large difference in the intensity ratio of the Qi(0) and Qi(l) Raman lines (due to transitions v=0 -» v-1, AJ= 0) for gaseous and solid hydrogen. A similar but more pronounced effect is observed 11 for deuterium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation